STUDI TENTANG SISTEM PERINGATAN DINI PERFORMANSI KEUANGAN PERUSAHAAN TERBUKA SEKTOR KONSTRUKSI, PROPERTI DAN REAL ESTAT DI BURSA EFEK JAKARTA - Muhammad Ali (InFestasi, 2006)
This research is aimed to understand: (1) Kinds of financialratios that discriminate takeover classification for the under leveredand Over levered firms and its critical point. (2) Kinds of financialratios that discriminate bankruptcy classification for the levered firmsand its critical point. The result of the research shows; There are 4financial ratios that discriminate takeover classification for the underlevered firms and its critical point are 0.731. There are 3 financialratios that discriminate bankruptcy classification for the Over leveredfirms and its critical point are 0.995